The effect of temperature on the male and female recombination landscape of barley. Issue 2 (7th August 2015) - Phillips, Dylan; Jenkins, Glyn; Macaulay, Malcolm; Nibau, Candida; Wnetrzak, Joanna; Fallding, Derek; Colas, Isabelle; Oakey, Helena; Waugh, Robbie; Ramsay, Luke
Summary Barley (Hordeum vulgare) is a crop of global significance. However, a third of the genes of barley are largely inaccessible to conventional breeding programmes as crossovers are localised to the ends of the chromosomes. This work examines whether crossovers can be shifted to more proximal regions simply by elevating growth temperature. We utilised a genome‐wide marker set for linkage analysis combined with cytological mapping of crossover events to examine the recombination landscape of plants grown at different temperatures. We found that barley shows heterochiasmy, that is, differences between female and male recombination frequencies. In addition, we found that elevated temperature significantly changes patterns of recombination in male meiosis only, with a repositioning of Class I crossovers determined by cytological mapping of HvMLH3 foci. We show that the length of synaptonemal complexes in male meiocytes increases in response to temperature. The results demonstrate that the distribution of crossover events are malleable and can be shifted to proximal regions by altering the growth temperature. The shift in recombination is the result of altering the distribution of Class I crossovers, but the higher recombination at elevated temperatures is potentially not the result of an increase in Class I events.